Darwin : an exceptional voyage - Grolleau, Fabien, 1972-; Royer, Jérémie, 1979-; Vick, Serafina (2019)
"When the young amateur naturalist Charles Darwin boarded the HMS Beagle in 1831, he had no idea what lay in store on his five-year voyage across the world. Darwin was disenchanted, moved, scandalised and awestruck by the vast discoveries that he made on his journey. On his return, he wrote his famous and controversial theory on the evolution of species. This long, perilous exploration was a journey that changed a man, and in doing so, the course of science itself."́--